Phosphorus Compounds in Translocating Phloem - Bieleski, R. L. (1969)
Phosphate-(32)P was introduced into a turnip leaf, and 3 hr later, the vascular bundles were stripped from the petiole and their phosphate ester pattern was studied. The pattern did not alter along their length and was like that of other tissues. Pumpkin leaves were painted with phosphate-(32)P; and later, the petioles were cut, the sieve tube exudates were collected and their phosphate ester patterns were studied. Exudates collected after 10 min had a high proportion of their (32)P present in P(i) and nucleoside triphosphates, while exudates collected after long translocation times (4-22 hr) had a lower proportion in these, and a higher proportion in hexose monophosphates and UDP glucose. In general, the ester patterns were like those of other tissues. The results indicate that sieve tubes are metabolically active, and that P(i) is the primary form in which phosphorus moves in the phloem.